Identification of Transgene-Free CRISPR-Edited Plants of Rice, Tomato, and Arabidopsis by Monitoring DsRED Fluorescence in Dry Seeds - Aliaga-Franco, Norma; Zhang, Cunjin; Presa, Silvia; Srivastava, Anjil K.; Granell, Antonio; Alabadí, David; Sadanandom, Ari; Blázquez, Miguel A.; Minguet, Eugenio G. (Frontiers in Plant Science, 2019)
Efficient elimination of the editing machinery remains a challenge in plant biotechnology after genome editing to minimize the probability of off-target mutations, but it is also important to deliver end users with edited plants free of foreign DNA. Using the modular cloning system Golden Braid we have included a fluorescence-dependent transgene monitoring module to the genome editing tool box. We have tested this approach in Solanum lycopersicum, Oryza sativa and Arabidopsis thaliana. We demonstrate that DsRED fluorescence visualization works efficiently in dry seeds as marker for the detection of the transgene in the three species allowing an efficient method for selecting transgene-free T2 dry seeds. We detected gene editing of selected targets in T2 plants, but more importantly, we identified homozygous gene edited plants with different mutations in the plant species tested. We demonstrate that this strategy allows rapid selection of transgene-free homozygous edited crop plants in a single generation after in vitro transformation.